Building students' historical literacies : learning to read and reason with historical texts and evidence - Nokes, Jeffery D. (New York, NY : Routledge, 2022)
This book explores the notion of historical literacy, adopts a research-based stance on literacy processes, and promotes the integration of content-area literacy instruction into history teaching. The new edition presents an examination of difficult histories and offers new strategies that can be applied to genres of historical inquiry.
Foreword by Tina Haefner Acknowledgements Part I Exploring the Critical Literacies used in Historical Inquiry Chapter 1 Why Teach Historical Literacies: Evaluating the Source and Context of this Book Chapter 2 Building Historical Literacies: A New Purpose for History Teaching Chapter 3 Defining Historical Literacies: What and How do Historians Read and Write?Chapter 4 Teaching Historical Literacies: Supporting Students as Active Readers and Writers Chapter 5 What is History? Establishing the Need for Historical Literacies in Historical InquiryChapter 6 Expanding Historical Literacies: Critically Reading Many Genres of EvidencePart II Strategies, Habits of Mind, Concepts, and TextsChapter 7 Using Critical Reading Strategies with Primary Sources Chapter 8 Helping Students Make Inferences with Artifacts Chapter 9 Teaching Historical Concepts with Visual Texts Chapter 10 Seeing Others$1 (BPerspectives Through Historical Fiction Chapter 11 Fostering Healthy Skepticism Using Textbooks and Secondary Sources Chapter 12 Exploring Historical Complexity With Audio and Video Texts Chapter 13 Building an Argument with Historical Numbers Chapter 14 Finding Patterns and Overcoming Barriers in Teaching Through Inquiry Indexs
Includes bibliographical references and index.
CoED
In English
Keywords: Historiography -- Study and teaching